Pricing and Capacity Provision in Electricity Markets: An Experimental Study - Chloé Le Coq; Henrik Orzen; Sebastian Schwenen (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2016)
The creation of adequate investment incentives has been of great concern in the restructuring of the electricity sector. However, to achieve this regulators have applied different market designs across countries and regions. In this paper we employ laboratory methods to explore the relationship between market design, capacity provision and pricing in electricity markets. Subjects act as firms, choosing their generation capacity and competing in uniform price auction markets. We compare three regulatory designs: (i) a baseline price cap system that restricts scarcity rents, (ii) a price spike regime that effectively lifts these restrictions, and (iii) a capacity market that directly rewards the provision of capacity. Restricting price spikes leads to underinvestment. In line with the regulatory intention both alternative designs lead to sufficient investment albeit at the cost of higher energy prices during peak periods and substantial capacity payments in the capacity market regime. To some extent these results confirm theoretical expectations. However, we also find lower than predicted spot market prices as sellers compete relatively intensely in capacities and prices. On the other hand, the capacity markets are less competitive than predicted.
Keywords: C91; L13; L94; 330; Price Cap; Experiment; Electricity; Supply Function Competition; Auctions